Designing for collaborative autonomy: updating user-centered design heuristics and evaluation methods. (September 2017) - Rayo, Michael F.
As we design automated and autonomous products that make increasingly sophisticated inferences and stronger interjections in a wider range of settings, it is increasingly critical to conceptualize these products as cognitive agents, and not simply as passive tools. Our repertoire of heuristics and techniques must expand to explicitly support not only a person's ability to take actions, but also to make sense of the world, determine the applicability of current and future plans, and select appropriate actions among many alternatives. These machine agents will also be expected to perform some or all of these functions themselves. Collectively, these attributes can be thought of as facilitating collaborative autonomy, in which all agents in the system can express initiative and cede authority based on their understanding of the world. However, product design is not the first discipline to face these problems or design these types of solutions. Cognitive Systems Engineering has been integrating and adding to the knowledge base in these areas for over 30 years. With some effort in translating their findings to our projects, we will be able to accelerate innovation and avoid the pitfalls and unintended consequences of previous attempts at increasing inference and interjection.